Identifikasi Tugas Dan Fungsi Data Stewardship Pada Dinas Komunikasi, Informatika Dan Persandian Aceh - Ima Dwitawati; Putri Nabila; Irfan Mutri Raazi (Prodi Teknologi Informasi UIN Ar-Raniry Bekerjasama dengan Pusat Penelitian dan Penerbitan LP2M Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
In the field of Information Technology, a person who has obligations regarding data security is known as data stewardship (data custodian). Data is the most important part that must be maintained and ensured its security. Therefore, institutions and organizations make various efforts in order to ensure the process of safeguarding and maintaining data, so that the data is safe and can avoid various errors and acts of misuse. This study aims to identify and document the roles, responsibilities and people involved as stewardship data at Diskominfo and Sandi Aceh. Data stewardship is grouped into 4 levels, namely external staff, internal staff, managers of internal institutions, and professionals who support data management. Where each level has specific responsibilities.